2017
DOI: 10.1111/jne.12489
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid receptor associates with pro‐inflammatory bias in the hippocampus of spontaneously hypertensive rats

Abstract: Damage observed in the hippocampus of the adult spontaneously hypertensive rat (SHR) resembles the neuropathology of mineralocorticoid-induced hypertension, supporting a similar endocrine dysfunction in both entities. In the present study, we tested the hypothesis that increased expression of the hippocampal mineralocorticoid receptor (MR) in SHR animals is associated with a prevalent expression of pro-inflammatory over anti-inflammatory factors. Accordingly, in the hippocampus, we measured mRNA expression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…71 Processes under the control of MR promote the initial phase of the stress reaction. 72 When the stress response proceeds, circulating glucocorticoid concentrations rise and the hormone starts, via GR, to prevent these initial defence reactions from overshooting and becoming damaging. 73 At the same time, this later GR-mediated action promotes memory consolidation of the experience.…”
Section: Mr and G R Fun C Ti On In B R Ainmentioning
confidence: 98%
See 1 more Smart Citation
“…71 Processes under the control of MR promote the initial phase of the stress reaction. 72 When the stress response proceeds, circulating glucocorticoid concentrations rise and the hormone starts, via GR, to prevent these initial defence reactions from overshooting and becoming damaging. 73 At the same time, this later GR-mediated action promotes memory consolidation of the experience.…”
Section: Mr and G R Fun C Ti On In B R Ainmentioning
confidence: 98%
“…63,64 In hippocampal CA1 pyramidal neurones, MR-induced excitability is suppressed and normalised by a genomic GR-mediated action and these opposing actions provide a U-shaped dose-response curve to corticosterone. 72 When the stress response proceeds, circulating glucocorticoid concentrations rise and the hormone starts, via GR, to prevent these initial defence reactions from overshooting and becoming damaging. Membrane MR-and genomic GR-mediated actions can cooperate and promote metaplasticity of basolateral amygdala neurones 67 ; this implies that excitability is rapidly increased via the membrane MR and subsequently maintained upon activation of the genomic GR.…”
Section: Mr and G R Fun C Ti On In B R Ainmentioning
confidence: 99%
“…However, as a newly identified heptapeptide of RAS, angiotensin-(1–7) (Ang-(1–7)), catalyzed by ACE2 from Ang II, is protective against inflammation and oxidative damage through binding with MasR, counteracting the deleterious effects of ACE/Ang II/AT1 pathway [4]. The spontaneously hypertensive rat (SHR), a widely used animal model of hypertension, exhibits neurological dysfunction, neuroimmune activation and oxidative brain damage [[5], [6], [7]]. The overactivated ACE/AngII/AT1 signaling but weakened ACE2/Ang(1–7)/MasR signaling also has been observed in the brain tissues of SHR, raising the possibility that rebalancing the RAS system might be neuroprotective [8].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the present study showed the improvement of learning and memory in response to repeated administration of mineralocorticoid receptor blockers in Aβ 1‐42 ‐treated mice. It is reported that the chronic blockade of mineralocorticoid receptors prevents neurodegenerative pro‐inflammatory cascade in the hippocampus [50], which is one of the most important pathogenic mechanisms involved in Aβ 1‐42 ‐induced cognitive deterioration [51]. Accordingly, it is possible to suggest that repeated administration of mineralocorticoid receptor may attenuate Aβ 1‐42 ‐induced neuroinflammation to prevent cognitive decline in an experimental model of dementia.…”
Section: Discussionmentioning
confidence: 99%